Photoshop CS6 Essential Skills - Galer, Mark; Andrews, Philip (Routledge, 2012)
Combining real word examples, step-by-step projects and professional advice, Photoshop CS6: Essential Skills provides you with the ultimate learning experience. Written by two internationally recognized authors and Adobe Photoshop Ambassadors, this book and DVD package gives you a guided tour of everything you need to know to master image editing and achieve stunning results. Broken into three parts, this self-study guide to Photoshop covers all the foundation skills to get you started, before moving on to more advanced image editing and photomontage techniques to develop you skills even further. A complete section of step-by-step imaging projects and the 12+ hours of DVD video tutorials will hone your image editing skills to give you professional quality results.
Online resource; Title from title page (viewed September 10, 2012)
Keywords: Adobe Photoshop; Photography -- Digital techniques; Computer graphics; Photographie numérique; Infographie; computer graphics; Photography; Digital techniques